Poetry of Witness and Translation: Claribel Alegría and Carloyn Forché - Raggio, Marcela María (2022)
American poet Carolyn Forché is also a human rights activist and a poetic translator. This article defines her poetics of translation as expressed in the Introduction to her anthology Against Forgetting. Twentieth-Century Poetry of Witness (1993), and her translation of Claribel Alegría’s Flowers from the Volcano (1982). The article presents the term “translation of witness” which has a social-political objective in Central America beyond literary transmission in the target language. The theoretical framework is based on Antoine Berman and Lawrence Venuti.